Influence Good Governance on Cooperative Performance in West Java - Istikomah Istikomah; Kartiwi Kartiwi (Fakultas Pendidikan Ekonomi dan Bisnis, 2022)
Cooperatives must be able to become the nation's economic strength that is able to improve the welfare of its members, and in the end can improve the economic welfare of the Indonesian nation. However, in reality, not all cooperatives develop as expected, and it is not uncommon for cooperatives to act as shields to seek profit for certain parties. Cooperative slump must be developed with good governance. Where there is a paradigm shift in society that was previously more on kinship leading to individualism. Therefore, the traditional management of cooperatives is no longer relevant, so it must improve with professional management. The purpose of this study is to analyzeinfluencegood corporate governanceon the performance of cooperatives in West Java. The population of this study is a cooperative located in West Java, the research method usesanalysis tool in the form of a Structural Equation Model (SEM) program through Smart PLS software. Samples were taken based on 10 times the number of items 31, namely as many as 310 samples. The results of the study show thatTransparency, Accountability, Independence and Fairness have a significant effect on cooperative performance, while Responsibility has no significant effect on cooperative performance.